An Analysis Regarding Properties and Health Benefits of Amla (International Journal of Food and Nutritional Sciences, 2022)
Phyllanthus emblica (Synonym: Emblica officinalis), often known as Indian gooseberry trees, has an important role in the treatment and management of illnesses and has been recorded since ancient times. It contains tannins, alkaloids, gallic acid, fiber, glucose, vitamin C, and is an excellent source of antioxidants. Because of its antioxidant properties, amla fruits are widely used to cure a variety of illnesses. Based on in vivo and in vitro research, Amla (Emblica officinalis) has a key role in lowering lipid peroxidation, oxidative stress, and reactive oxygen species, and increasing antioxidant levels, ultimately inhibiting pathogenesis. Its antioxidant, anti-inflammatory, hepatoprotective, gastroprotective, anti-diabetic, antibacterial, neuroprotective, cardioprotective, and immunomodulatory properties have been shown. Furthermore, many research have shown its function in cancer management. Through a review of in vivo and in vitro studies, this review comprehensively summarizes the function of Amla (Emblica officinalis) in illness treatment and management.